Hello!
In this case, you are looking for a value of K so the left side of the equation is equal to the right.
The left side of the equation is K (3x - 2), and the right is 4 - 6x. To get the left side to equal the right, you can set K = -2. This is because of the distributive property: a number just outside of the parenthesis can distribute to everything in the parenthesis like so:
-2 (3x - 2) = (-2 * 3x) - (-2 * -2) = -6x + 4
Therefore, your answer is K = -2.
Hope this helps!
(Side note: a better way to do this would be to divide both sides by 3x - 2)